2012
DOI: 10.3852/11-084
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of the phenylacetic acid metabolic complex in the pathogenic activity of Rhizoctonia solani anastomosis group 3

Abstract: The soil fungus Rhizoctonia solani produces phytotoxic phenylacetic acid (PAA) and hydroxy (OH-) and methoxy (MeO-) derivatives of PAA. However, limited information is available on the specific role that these compounds play in the development of Rhizoctonia disease symptoms and concentration(s) required to induce a host response. Reports that PAA inhibits the growth of R. solani conflict with the established ability of the fungus to produce and metabolize PAA. Experiments were conducted to clarify the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The activity of MTPA was relatively stable in the range of pH levels 3.5–7.0 and decreased significantly beyond these limits. The minimum activity was observed above pH 7.0 contrary to Bartz et al (2012) who observed that the optimal pH for the activity of phenylacetic acid (PAA) from R. solani infected tomato plant was 5.5. This suggests that the activity of MTPA may be due to their acidic nature.…”
Section: Discussionmentioning
confidence: 58%
“…The activity of MTPA was relatively stable in the range of pH levels 3.5–7.0 and decreased significantly beyond these limits. The minimum activity was observed above pH 7.0 contrary to Bartz et al (2012) who observed that the optimal pH for the activity of phenylacetic acid (PAA) from R. solani infected tomato plant was 5.5. This suggests that the activity of MTPA may be due to their acidic nature.…”
Section: Discussionmentioning
confidence: 58%
“…To obtain further insights into the putative activities of vitamin B6, we also assessed whether the relative transcripts abundance of RsolPDX1, RsolPDX2 , and RsolPLR are regulated by PAA, an antimicrobial and antioxidant compound produced by R. solani AG3 (Bartz et al, 2012 ). The three genes were mostly down-regulated in the range of 5.0–1.5 fold at 24 and 72 HPT, respectively (Figures 7C,F,I ).…”
Section: Resultsmentioning
confidence: 99%
“…No amendment was added to the half-strength PDB media in the control plates. Oxidant sensitivity and effective concentrations (EC 50 ) for H 2 O 2 and paraquat were determined by obtaining dose-response curves and the concentration which resulted in near 50% inhibition of R. solani growth at 72 hours post treatment (HPT) (Wang et al, 2011 ), whereas the concentration of applied PAA was selected based on previous reports (Bartz et al, 2012 ). The vitamin B6 vitamers were chosen based on optimized concentrations that do not inhibit the growth of R. solani .…”
Section: Methodsmentioning
confidence: 99%
“…Agar plugs from starter cultures were placed on PDA in Petri dishes (9 cm in diameters) and grown at 28°C in the dark. Based on the results of previous research, the concentration of PAA used for this study was set as 7.34 mM [ 23 ]. The PAA solution was prepared by dissolving 0.1 g of PAA (chemically pure) in 100 ml of distilled water and was filtrated through 0.22 μm filters.…”
Section: Methodsmentioning
confidence: 99%